Il fondamento dell’identità nella dialettica tra memoria e ricordo - Helzel, Paola B. (Bollettino Filosofico, 2016)
Today’s society lives in constant worry of losing something, so it seems mandatory looking into the past to find elements of identity and prospects for the future. All of this has resulted in the categorical imperative of keeping and preserve all signs of memory. Memory, indeed, has become the central theme, as in a cultural sphere as in the political debate. Memory, since it is able to preserve and reminding as a vector of senses, is a key condition of humanity. A memory, product of experiences and testimony to the sense of the things done and transmitted, it’s able of becoming a reminder. An act of conscience by which we reconstruct a certain portion of our past. Without memory and reminding there cannot be identity.